The Development Of Regionalism And Political Pluralism In Central Asia - Sharaf Agabaev (Genius Journals, 2025)
This scientific article focuses on further expanding regional cooperation in Central Asia amidst the current globalization process, including further developing political dialogue, jointly developing programs and projects in trade, investment, transport-logistics, energy, agriculture, and addressing environmental issues, and further increasing activity in the cultural and humanitarian spheres. It emphasizes that these efforts serve as a crucial foundation for ensuring socio-political stability in the region. Furthermore, the article scientifically reveals that the concept of regionalization, the process of developing cooperation in economic, political, cultural, and security spheres among states in a specific geographical area, is interpreted based on theories such as neofunctionalism, intergovernmentalism, and constructivism. It also explores the formation of regional organizations, norms, and cooperation mechanisms, as well as regional issues at various levels, from free trade zones to political alliances
Keywords: Concept of regionalism; regional culture; politics